Description Of The Level Of Patient Satisfaction With Health Services In The Inpatient Unit Of Rsu Mayjen H.A Thalib Kerinci - Lorenza, Putri Suci; Mawarti, Indah; Oktarina, Yosi (Jurnal Keperawatan Universitas Jambi, 2024)
Low levels of patient satisfaction affect hospital development. When medical services are unsatisfactory, patients move to another hospital. At Mayjen H.A Talib Hospital, Kerinci Regency, several patients complained about the cleanliness of the room and the response of the nurses. Data shows a decrease in the number of visits every year due to dissatisfaction with health services. This study aims to find out the descriptionof patient satisfaction with health services in the Internal Medicine, ENT and Surgery inpatient units at RSU Mayjen H.A Talib, KerinciRegency. This research uses a quantitative descriptive research with univariate analysis, using a servqual questionnaire based on 5 dimensions.Non-probability sampling technique using purposive sampling, a sample of 87 patients in the Internal Medicine, ENT and Surgery wards atthe Mayjen H.A Talib General Hospital, Kerinci Regency, in February-March 2022. The results obtained in this study show patientsatisfaction indicators show: tangible 65.22% satisfactory, reliability 62.38% unsatisfactory, responsiveness 58.72% unsatisfactory, assurance 71.48% satisfactory, empathy 63.01% unsatisfactory. Of the 5 dimensions, 2 dimensions satisfy the patient, 1 dimension is not satisfactory. It is hoped that the five dimensions will be improved and optimized to achieve patient satisfaction.